KINERJA STAF UNIT PELAYANAN PERSETUJUAN BANGUNAN GEDUNG (PBG) PADA DINAS PENATAAN RUANG KOTA SEMARANG - Muhammad Rizqi Maulana; Satria Aji Imawan (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The importance of staff performance in the implementation of public services is particularly evident in the Building Approval Service Unit (Persetujuan Bangunan Gedung/PBG) at the Semarang City Spatial Planning Office, which is required to provide services that are effective, efficient, and responsive to community needs. This study aims to analyze staff performance in the implementation of PBG services and to identify the factors influencing such performance. The research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. Data analysis is conducted through the stages of data reduction, data presentation, and systematic conclusion drawing. The results indicate that, in general, the performance of PBG service staff has been relatively good, as reflected in aspects of productivity, service quality, responsiveness, and the utilization of information technology systems. However, several challenges remain, including delays in data updates, technical disruptions in the system, and less-than-optimal responsiveness in addressing public concerns. In addition, the ability to adapt to policy changes and consistency in implementing standard operating procedures still need improvement. The study concludes that although the performance of PBG service staff shows a positive trend, continuous improvement efforts are necessary through enhancing human resource capacity, optimizing service systems, and strengthening internal supervision to achieve higher-quality public services that are oriented toward community satisfaction.